First occurrence of Anacroneuria singularis Righi-Cavallaro & Lecci, 2010 (Plecoptera: Perlidae) in Rondônia, western Amazonia, Brazil - Firmino, Viviane Caetano; Ribeiro, José Moacir Ferreira; Santos, Emerson Monteiro Dos; Juen, Leandro (Zootaxa, 2019)
Anacroneuria singularis is newly reported from the northern Brazilian state of Rondônia in the western Amazonia. Records for this species are also reported for the central-western and southeastern regions of Brazil. Knowledge of the distribution of a species is fundamental for allowing better conservation planning, especially the identification of nymphs which can be used to evaluate water quality of Amazonian streams.